Comparison of growth inhibition and immunofluorescence tests in serotyping clinical isolates of Ureaplasma urealyticum. Issue 3 (June 1977) - Piot, P
Abstract : Typestrains of the eight serotypes of Ureaplasma urealyticum and 39 genital isolates were typed by the growth inhibition (GI) and indirect immunofluorescence (IF) tests. The GI test proved to be very specific and simple, demanding large volumes of serum. It was less sensitive than the IF test, which produced more cross-reactions, was economical in serum, and able to detect mixed infections. Of the 39 isolates, 27 were serotyped by GI and 34 by IF. Mixed cultures occurred in as many as 36% of the isolates.